2021
DOI: 10.19080/gjorm.2021.08.555737
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the Physiological CTG Interpretation & Hypoxia in Labour (HIL) Tool, and its Incorporation into a Software Programme: Impact on Perinatal Outcomes

Abstract: Each Baby Counts Reports in the UK from 2016-2021 have consistently highlighted that 33% of intrapartum related perinatal deaths and severe hypoxic ischaemic injuries in the UK were due to CTG misinterpretation. Moreover, in approximately 72% of cases, a different care may have given rise to different outcomes. International consensus guidelines on Physiological Interpretation of the CTG produced by 34 CTG experts from 14 countries was aimed at individualisation of care by considering the compensatory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…On the other hand, simply transposing some principles from Physiological CTG Masterclasses, without fundamentally changing the CTG interpretation tool-based knowledge of fetal physiology may lead to confusion resulting in poor maternal and perinatal outcomes. Although, there have been several publications on Physiological Interpretation of CTG prior the publication of the revised NICE CTG Guideline , including improvement in outcomes following the implemen-tation of Physiological Interpretation of the CTG [55][56][57][58][59][60][61], it is indeed regrettable that this revised guideline has disregarded these principles of physiological CTG interpretation. Merely lifting "How is the Baby?"…”
Section: Recently Revised and Updated Nice Ctg Guideline (Dec 2022)mentioning
confidence: 99%
“…On the other hand, simply transposing some principles from Physiological CTG Masterclasses, without fundamentally changing the CTG interpretation tool-based knowledge of fetal physiology may lead to confusion resulting in poor maternal and perinatal outcomes. Although, there have been several publications on Physiological Interpretation of CTG prior the publication of the revised NICE CTG Guideline , including improvement in outcomes following the implemen-tation of Physiological Interpretation of the CTG [55][56][57][58][59][60][61], it is indeed regrettable that this revised guideline has disregarded these principles of physiological CTG interpretation. Merely lifting "How is the Baby?"…”
Section: Recently Revised and Updated Nice Ctg Guideline (Dec 2022)mentioning
confidence: 99%
“…If the training in physiological interpretation of CTG is to be effective, then the tools to interpret CTG traces whilst using the STAN technology should mirror what is taught during the training. There have been several publications supporting the use of physiological interpretation of CTG [44][45][46][47][48][49][50][51][52][53][54], and therefore, failure to change the CTG STAN interpretation tool to improve maternal and perinatal outcomes cannot be justified in the era of evidence-based clinical practice, founded on sound scientific principles. It has been reported that fetal ECG changes occur in approximately 40% of subacute hypoxia during second stage of labour [55], and therefore, the use of the same CTG interpretation tool with the same parameters without considering the different types of hypoxia, may lead to poor outcomes when the hypoxic stress rapidly evolves during the second stage of labour.…”
Section: Is Stan Clinically and Scientifically Dead Requiring A Requiem?mentioning
confidence: 99%
“…CTG analysis and interpretation is performed visually by obstetricians and midwives following guidelines [ 2 ]. There are different classifications with varying characteristics [ 2 – 6 ], without clear international consensus among them [ 7 10 ]. Although the guidelines are constantly being challenged and reviewed [ 11 , 12 ], the overall process of interpreting CTG during delivery is known to be subjective and to induce a significant interobserver and intraobserver variability [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%